Penerapan Pendekatan Realistic Mathematics Education untuk Meningkatkan Belief Matematika di Kelas V Sekolah Dasar - Syafiri, Rahmi; -, Fadhilaturrahmi; Hardi, Vitri Angraini; Rizal, Muhammad Syahrul; -, Sumianto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The background of this research is the low mathematic belief & disposition of mathematics in fifth grade students of UPT SDN 012 Salo. One solution to overcome this problem is to use a Realistic Mathematics Education approach. The purpose of this study was to describe the increase in mathematical belief & disposition of mathematics using the rme approach in fifth grade students at SDN 012 Salo. This research method is Classroom Action Research which is carried out in three cycles. Each cycle consists of 2 meetings and four stages, namely planning, implementing, observing, reflecting, and the time the research was carried out from 24 to 30 May 2023. Subjects in this study were 19 class V students, with the number of males - 6 male students, and 13 female students. Data collection techniques in the form of documentation, observation, and questions. The results of this study can be concluded that the mathematical belief & disposition of mathematics using the (RME) approach. The results of the belief questionnaire in cycle I averaged 49.42% in the low category. Furthermore, the disposition criteria with a total an average percentage of 38.52% are in the low category. The results of the cycle II belief questionnaire can be seen from students' mathematical beliefs with an average percentage of 57.84% in the low category. Furthermore, based on the criteria of mathematical disposition with a to an average percentage of 47.89% in the medium category. The results of the belief questionnaire in cycle III saw students' mathematical beliefs with a total score of an average percentage of 75.58% in the medium category. Thus it can be concluded that using a RME approach can improve mathematical beliefs & mathematical dispositions students class V UPT SDN 012 Salo.